PELAKSANAAN PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENGGELAPAN CPO (CRUDE PALM OIL) DI WILAYAH HUKUM POLISI RESOR KOTA DUMAI - Muhammad Afdhol; Syaifullah Yophi A; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Law enforcement is a process for the enforcement of remedies, or functioning of legal norms to guide behavior in real traffic or legal relations connected with the community and state . Law enforcement can be viewed from two angles , namely in terms of subject and object . Law enforcement against criminal acts of CPO’s (Crude Palm Oil) froaud in the police jurisdiction Dumai Downstream resort has done well even though there are still deficiencies that must be addressed due to the fact that many law enforcement theories that are not in line with the practice in the field.Keywords: Law Enforcement - Crime – Froaud